LOWER BOUND OF THE ESSENTIAL SPECTRUM OF A FAMILY OF 3X3 OPERATOR MATRICES - Tosheva, Nargiza (Центр Научных Публикаций (buxdu.uz), 2023)
Block operator matrices are matrices the entries of which are linear operators between Banach or Hilbert spaces [1, 2]. Every bounded linear operator can be written as a block operator matrix if the space in which it acts is decomposed in two or more more components